Peran TIK bagi Pendidik dalam Dunia Pendidikan - Tyastuti, Dwi; Oktavia, Gadis; Aprilliyani, Widiya; Alya, Fakhira; Rahmasari, Laila; Hidayati, Isna Wahyu (Lembaga Yasin AlSys, 2023)
Data communication technology (ICT) is currently influencing every aspect of people's lives. They play a significant position in the place of activity, business, education, and entertainment. Also, many people identify ICT as a driving force for change; changes in activity situations, prosecution and data alteration, learning methods, approaches to teaching and learning activities, objective research, and in accessing data communication technology. In this digital age, the use of ICT in categories is important for providing opportunities for students to practice and practice the necessary 21st century skills. ICT enhances learning and teaching and learning activities and their importance for teachers in carrying out their role as inventors of pedagogical fields. ICT helps a teacher to convey his teaching in an interesting and learnable way for teaching participants at every level of the educational program. In making educational nursery upgrading programs useful and interesting as ICT. Data and Communication Technologies (ICT) exemplified by the internet and interactive multimedia are clearly an important focus for future education and need to be integrated effectively into learning and formal teaching and learning activities, especially in teacher education institutions.